To the Question of the Strategy of Stable Development as the Theoretically-Methodological Basis of Ecological Education - S А Stepanov (Peoples' Friendship University of Russia (RUDN University), 2008)
The article considers the essence and features of ecologically-oriented education for the formation of the ecological culture taking into account the basic provisions of «The Strategy of the European economic commission of the United Nations for the education in the interests of the steady development».